THE EFFECT OF IMMERSING OF TUNA FISH FILLET (Euthynnus affinis) INTO THE LIQUID SMOKE SOLUTION ON THE QUALITY OF FISH NUGGET - Shafa Yasmin Vazilla; Tjipto Leksono; Dian Iriani (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACT Tuna fish is showing a high quantity of production and also has valuable nutrient contents. Fish nugget is one of the most popular forms of fishery product diversification. However, it is possible to develop nuggets more to provide consumers with a wide choice of flavors. One way to add the flavor of nugget is by adding smoked flavor to tuna fish nuggets. The adding of liquid smoke into the fish product is a way to produce smoke flavored fish nugget safely for health. This research aimed to observe the effect of fish fillet immersion into the liquid smoke solution at varied combination of concentration and immersion time on the quality of the fish nugget and to determine the best treatment to produce the most preferred tuna nugget by consumers. The research used an experimental method and designed for a Completely Randomized Design to conduct the treatment of fish fillet immersion into the liquid smoke solution at 5 varied concentration and immersion time combinations, based on a preliminary study, namely: 2% for 30 minutes (K2L30), 2% for 60 minutes (K2L60), 4% for 30 minutes (K4L30), 4% for 60 minutes (K4L60), and without immersion as the control. The result showed that the treatment of immersing the fish fillet into the liquid smoke solution at the concentration of 2% for 30 minutes (K2L30) produced the best quality of tuna fish nugget and the highest consumer preference. This fish nugget contained 56.0% moisture, appropriated to the provision in Indonesian National Standard (SNI) for fish nugget. The product is also showing as the safely food, showed by the content of total phenol at 26,2 ppm or equivalent (0.00262-0.00543%), which is still far below the maximum level allowed for total phenol in food (0.02-0.1%), pH 5,90, and no Staphylococcus aureus bacteria contaminated. Keywords: fish nugget, flavor, immersion, liquid smoke